Preparation method and application of boron-doped flaky defective niobium-titanium-oxygen material growing on carbon tube

By using boron-doped sheet-like defective niobium titanium oxide material grown on carbon tubes as the positive electrode material in lithium selenium batteries, the problem of poor cycle stability of lithium selenium batteries is solved, and higher cycle performance and fast charging performance are achieved.

CN119852413AActive Publication Date: 2025-04-18HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510078243.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

Lithium selenium batteries have volume expansion/shrinkage problems, low catalytic kinetics, low selenium utilization rate and poor cycle stability during charging and discharging, which hinder their commercialization.

Method used

Boron-doped sheet-like defective niobium titanium oxide grown on carbon tubes is used as the positive electrode material, and the conversion efficiency of the active substance selenium is synergistically improved through physical domain limitation, chemical adsorption and catalytic conversion.

Benefits of technology

It significantly improves the circulation performance and fast charging performance of lithium selenium batteries, enhances the utilization rate of active substances, and reduces equipment requirements and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852413A_ABST
    Figure CN119852413A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a boron-doped flaky defective niobium-titanium-oxygen material growing on a carbon tube, and belongs to the technical field of lithium-selenium battery positive electrode materials, the method comprises the following steps: dissolving a niobium source, a titanium source and a carbon nanotube in an organic solvent, adding a surfactant, then adding an alkali source, and carrying out liquid-phase mixing and stirring to obtain the boron-doped flaky defective niobium-titanium-oxygen material growing on the carbon tube. Transferring into a reaction kettle, and reacting at a certain temperature and pressure to generate a composite precursor; and putting the precursor and a boron source into a tubular furnace, and calcining at high temperature to obtain the boron-doped flaky defect niobium titanium oxygen composite material growing on the carbon tube. Then the niobium-titanium-oxygen composite material reacts with selenium to generate a selenium and boron-doped sheet-shaped defect niobium-titanium-oxygen composite material growing on a carbon tube, the selenium and boron-doped sheet-shaped defect niobium-titanium-oxygen composite material serves as a positive electrode active material of the lithium-selenium battery, the sheet-shaped structure, boron doping and oxygen deficiency can remarkably enhance the reaction activity of a substrate plane, formation and dissolution of Li2S are promoted, and the cycle performance and rate capability of the lithium-selenium battery are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium-selenium battery positive electrode materials, and relates to a preparation method of a boron-doped sheet-defect niobium-titanium oxide material grown on a carbon tube and its application in lithium-selenium batteries. Background Art

[0002] In recent years, the growing demand for high energy density energy storage devices has stimulated the exploration of next-generation lithium-ion battery alternatives. Among the many candidate batteries, lithium-sulfur batteries have attracted great attention due to their high theoretical energy density. As a cognate element of S, Se has a high capacity comparable to that of S (Se, 3268 mAh cm -3 vs S,3467mAh cm -3 ), and its conductivity is about 1025 times higher than that of S (Se, 1×10 -5 S cm -1 vs S,5×10 -30 S cm -1 ), which can achieve faster kinetic characteristics. However, the commercialization of lithium-selenium batteries has been hampered by the large density difference between selenium and the discharge product lithium selenide during the charge and discharge process, the volume expansion / contraction problem, the low catalytic reaction kinetics, the low utilization rate of selenium, and the poor cycle stability caused by the shuttling between the positive and negative electrodes.

[0003] In order to solve the above problems, researchers have designed and synthesized carbon materials with various structures, such as hollow carbon, porous carbon, graphene and carbon nanotubes. However, due to the weak interaction between traditional carbon materials and polyselenides, the long-term cycle stability and power characteristics of the battery are insufficient. Therefore, the development of a polar material with strong polarity and high catalytic activity and the composite with carbon materials are expected to better modify the existing selenium positive electrode and improve the utilization rate of active materials and cycle performance of lithium-selenium batteries. Summary of the invention

[0004] In order to improve the utilization rate of active materials and the cycle performance of lithium-selenium batteries, the present invention provides a preparation method of a boron-doped flaky defect niobium-titanium oxide material grown on a carbon tube and its application in lithium-selenium batteries. The specific structure can synergistically improve the conversion efficiency of the active substance selenium through physical confinement, chemical adsorption and catalytic conversion. The lithium-selenium battery using the composite positive electrode has excellent cycle performance and fast charging performance.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a boron-doped flaky defective niobium-titanium oxide material grown on a carbon tube comprises the following steps:

[0007] Step 1, weighing a niobium source and a titanium source in a molar ratio of 2:1, adding them to an organic solvent containing single-walled carbon nanotubes and stirring them evenly, then adding a surfactant and an alkali source, and then stirring them at room temperature to make them evenly mixed, and then transferring the mixed solution to a reaction kettle, placing it in a homogeneous reactor at 150-210° C. to react for 12-36 hours, and after the reaction is completed, centrifuging the product with anhydrous ethanol, the centrifuge speed is 5500-8500 r / min, and the centrifugation time is 4-8 minutes each time, and then drying to obtain a titanium niobium oxide composite precursor grown on the carbon tube;

[0008] The mass ratio of the sum of the niobium source and the titanium source to the carbon tube is 0.2-0.5:1;

[0009] The niobium source is one of niobium ethoxide, niobium pentachloride, ammonium niobate oxalate and niobium oxalate;

[0010] The titanium source is one of titanium sulfate, metatitanic acid, tetrabutyl titanate and isopropyl titanate;

[0011] The organic solvent is one or more of ethanol, methanol, cyclohexane, isopropanol, glycerol, tetrahydrofuran, N-methylpyrrolidone and ethylene glycol;

[0012] The surfactant is one of urotropine, cetyltrimethylammonium bromide, ethanolamine and polyvinylpyrrolidone;

[0013] The alkali source is ammonia water, potassium hydroxide and sodium hydroxide;

[0014] The molar ratio of the alkali source is 1.5-6 times that of the niobium source, and the amount of the surfactant is 3-5 times that of the niobium source;

[0015] Step 2: Place the titanium niobium oxide composite precursor grown on the prepared carbon tube and the boron source in two magnetic boats in a certain proportion, and then transfer them to a tubular furnace for high-temperature calcination treatment. The calcination temperature is 600-900°C and the calcination time is 3-8h. Boron-doped flaky defect niobium titanium oxide material B-TiNb2O7@CNT grown on the carbon tube can be obtained.

[0016] The boron source is one of sodium borohydride, boron powder and boron dioxide;

[0017] The mass ratio of the titanium niobium oxide composite precursor grown on the carbon tube to the boron powder is 1:0.6-1.8;

[0018] The protective atmosphere of the tubular furnace is a mixed gas of argon and hydrogen (the volume ratio of argon and hydrogen is 95%:5%), argon, nitrogen, vacuum atmosphere or one of the above;

[0019] An application of a boron-doped flaky defect niobium-titanium oxide material grown on a carbon tube prepared by the preparation method, wherein the boron-doped flaky defect niobium-titanium oxide material grown on a carbon tube is composited with selenium powder and used as a positive electrode material for a lithium-selenium battery, or is used alone as a catalyst for the adsorption of polyselenides.

[0020] When applied to lithium-selenium batteries, the specific application method is: the boron-doped flaky defect niobium-titanium oxide material grown on the carbon tube and the active material selenium powder are ground and mixed into a uniform powder, the powder is placed on a magnetic boat, and transferred to a tubular furnace in an argon atmosphere for constant temperature and high-temperature calcination; it is naturally cooled to room temperature and taken out to obtain a selenium- and boron-doped flaky defect niobium-titanium composite material grown on the carbon tube, which is used as the positive electrode material of the lithium-selenium battery.

[0021] The mass ratio of the boron-doped flaky defect niobium-titanium oxide material grown on the carbon tube to the active material selenium powder is 3-5:2-1; the constant temperature of the tube furnace is 240-270° C., and the constant temperature time is 10-18 hours.

[0022] The generated selenium and boron doped flaky defect niobium titanium oxide composite material grown on the carbon tube is dispersed in a solvent as an active material with a conductive agent and a binder to obtain a positive electrode slurry, and the slurry is coated on the positive electrode collector, dried, rolled and punched to obtain a positive electrode sheet, and then a button battery is assembled.

[0023] The binder is polyvinylidene fluoride (PVDF) or an aqueous dispersion of acrylonitrile multi-polymer (LA133), the conductive agent is acetylene black, and the solvent is N-methylpyrrolidone (NMP) or ultrapure water.

[0024] The mass ratio of positive electrode active material: conductive agent: binder is 70%-90%: 5%-20%: 5%-10%. Preferably, the mass ratio of active material: conductive agent: binder is 80%: 10%: 10%.

[0025] The operating temperature range of the lithium selenium battery is -30°C to 55°C.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1) The present invention provides a selenium-based composite material, which includes boron-doped defective niobium titanium oxide with a two-dimensional sheet structure, nanotube-shaped carbon, and selenium loaded in carbon nanotubes. Compared with traditional non-polar carbon materials, the niobium titanium oxide material grown on the carbon tube can adsorb polyselenides and inhibit the "shuttle effect" through physical confinement and strong chemical bonding characteristics; and boron doping can produce an empty σ orbital perpendicular to the substrate plane, maximizing the overlap with the frontal orbit of Se; the sheet structure and boron doping can significantly enhance the reaction activity of the substrate plane, promote the conversion of polyselenides to the final product, and enhance the cycle performance of lithium-selenium batteries.

[0028] 2) The preparation method of the present invention is simple, has mild conditions, a coherent process, strong controllability, low cost, low requirements on equipment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the XRD pattern of the boron-doped niobium-titanium oxide material grown on carbon tubes with plate-like defects synthesized in Example 1;

[0030] Figure 2 This is a SEM image of the boron-doped niobium-titanium oxide material grown on carbon tubes and having plate-like defects synthesized in Example 1;

[0031] Figure 3 The cycle performance of the lithium-selenium battery of Example 1 at 0.5C;

[0032] Figure 4 The charge and discharge capacities of the lithium-selenium battery of Example 2 at different rates. DETAILED DESCRIPTION

[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Embodiment 1:

[0035] The synthesis of a boron-doped flaky defect niobium-titanium oxide material grown on a carbon tube comprises the following steps:

[0036] Step 1: Dissolve 0.4g of niobium pentachloride, 0.252g of tetrabutyl titanate and 1.96g of single-walled carbon nanotubes in a mixed solution consisting of 25mL of ethylene glycol and 10mL of isopropanol, and place on a magnetic stirrer for continuous stirring for 30min. Subsequently, add 0.98g of urotropine and 0.4g of sodium hydroxide to the mixed solution, stir at 30°C for 5h to mix evenly, then transfer it to a 50mL reactor, and heat it continuously at 190°C in a homogeneous reactor for 24h. After the reaction is completed, collect the product by centrifugation with anhydrous ethanol, collect the product after centrifugation at 7000rpm for 5 times, and transfer the product to a vacuum oven for drying to obtain a titanium niobium oxide composite precursor grown on the carbon tube;

[0037] Step 2: The titanium niobium oxide composite precursor grown on the prepared carbon tube and the boron powder were weighed in a mass ratio of 1:0.8, and the powders were placed in two magnetic boats respectively, and transferred to the argon atmosphere in the tube furnace at 5°C min -1 The temperature is raised to 750℃ at a rate of 100℃ and then calcined at 750℃ for 4h to obtain boron-doped flaky defective niobium-titanium oxide material grown on carbon tubes. The XRD spectrum is shown in Figure 1 As shown, the positions of all diffraction peaks in the figure are consistent with the TiNb2O7 (JCPDS card no.77-1374) standard card. Figure 2 The SEM image of the boron-doped niobium titanium oxide material grown on carbon nanotubes shows that the niobium titanium oxide grows in the form of flakes on the carbon nanotube substrate, with the length of the flakes being about 500 nm.

[0038] The boron-doped flaky defect niobium titanium oxide material grown on the carbon tube obtained in this embodiment and the selenium powder composite are used as positive electrode materials in lithium-selenium batteries, or used alone as catalysts for the adsorption of polyselenides to inhibit the "shuttle effect" between polyselenides and improve the active material utilization and cycle stability of lithium-selenium batteries.

[0039] The specific application method is: the prepared boron-doped flaky defect niobium titanium oxide material grown on carbon tubes is uniformly mixed with selenium powder in a mass ratio of 3:2. Add it into an agate mortar and grind it for 20 minutes to finally fully mix it into a powder with uniform color. Pour the mixture onto weighing paper, transfer it to a magnetic boat, place it in an argon atmosphere in a tube furnace, and heat it at 2℃ min -1 The sample was heated to 260°C at a heating rate of 1000 ℃ and calcined at a constant temperature of 260°C for 12 hours. After the time was up, the sample was allowed to stand and naturally cooled to room temperature and then taken out to obtain a mixture of selenium- and boron-doped flaky defective niobium-titanium oxide grown on carbon nanotubes.

[0040] A mixture of selenium- and boron-doped flaky defective niobium-titanium oxide grown on carbon nanotubes was used as the positive electrode active material of the lithium-selenium battery, metallic lithium was used as the negative electrode, and the commercial ether electrolyte was used in an amount of 10uLmg -1 , assembled lithium selenium batteries and tested the electrochemical performance. The cycling stability at 0.5C is shown in Figure 3 As shown, the discharge capacity of the first cycle of 0.5C activation is 587.4 mAhg -1 The first coulombic efficiency is 90.4%, and even at the 80th cycle, the discharge capacity is 459.1 mAh g -1 , higher than pure carbon tube lithium selenium battery (130mAhg -1 ), indicating that the lithium-selenium battery assembled in Example 1 of the present invention has good cycle stability.

[0041] Example 2

[0042] The difference between this embodiment and embodiment 1 is that the mixed solvent of 25 mL ethylene glycol and 10 mL isopropanol is replaced with 35 mL ethanol. In addition, hexadecylammonium bromide is added instead of urotropine, and the reaction condition is to react at 180°C for 16 hours. The remaining parameters are the same as those in embodiment 1. The prepared mixture of selenium and boron-doped sheet-shaped defective niobium titanium oxide grown on carbon tubes is used as the positive electrode active material of lithium selenium battery to assemble lithium selenium battery and test the electrochemical performance. Cyclic stability at 0.5C is as follows Figure 4 As shown, the discharge capacity at 0.5C is 616.8 mAhg -1 Even when the discharge rate is 3C, the discharge capacity is 454.0mAhg -1 , indicating that the lithium-selenium battery composed of the composite positive electrode has excellent fast charging characteristics.

[0043] Example 3

[0044] The difference between this embodiment and embodiment 1 is that: the mixed solvent of 25 mL of ethylene glycol and 10 mL of isopropanol is changed to 20 mL of isopropanol and 10 mL of glycerol, in addition, hexadecylammonium bromide is added instead of hexamine, the reaction conditions are to react at 190° C. for 16 h, the added alkali is changed from sodium hydroxide to ammonia water, the added boron source is changed to sodium borohydride, the mass ratio of the titanium niobium oxide composite precursor grown on the carbon tube to the boron powder is changed to 1:0.5, and the other parameters are the same as those in embodiment 1.

[0045] Example 4

[0046] The difference between this embodiment and embodiment 1 is that: the mixed solvent of 25 mL of ethylene glycol and 10 mL of isopropanol is changed to 35 mL of N-methylpyrrolidone, in addition, hexadecylammonium bromide is added instead of hexamine, the added alkali is changed from sodium hydroxide to ammonia water, the mass ratio of the titanium niobium oxide composite precursor grown on the carbon tube to the boron powder is changed to 1:1.2, and the other parameters are the same as those in embodiment 1.

[0047] Example 5

[0048] The difference between this embodiment and embodiment 1 is that the mixed solvent of 25 mL of ethylene glycol and 10 mL of isopropanol is changed to 20 mL of isopropanol and 10 mL of methanol, in addition, instead of adding urotropine, polyvinyl pyrrolidone is added, the reaction conditions are changed to react at 200° C. for 24 h, the added alkali is changed from sodium hydroxide to potassium hydroxide, the mass ratio of the titanium niobium oxide composite precursor grown on the carbon tube to the boron powder is changed to 1:1, and the other parameters are the same as in embodiment 1.

[0049] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a boron-doped flaky defect niobium-titanium oxide material grown on a carbon tube, characterized in that: The following steps are involved: Step 1, adding a niobium source and a titanium source in a molar ratio of 2:1 to an organic solvent containing single-walled carbon nanotubes and stirring evenly, and then adding a surfactant and an alkali source and stirring evenly to obtain a mixed solution; Step 2: Transfer the mixed solution to a reaction kettle, place it in a homogeneous reactor and react at 150-210° C. for 12-36 hours; Step 3: After the reaction is completed, the solid is collected by centrifugation and dried to obtain a titanium niobium oxide composite precursor grown on the carbon tube; Step 4: Place the titanium niobium oxide composite precursor grown on the carbon tube and the boron source in two magnetic boats respectively and transfer them to a tube furnace for high-temperature calcination to obtain boron-doped flaky defective niobium titanium oxide material grown on the carbon tube.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the sum of the niobium source and the titanium source to the carbon tube is 0.2-0.5:

1.

3. The preparation method according to claim 1, characterized in that: In step 1, the niobium source is one of niobium ethanol, niobium pentachloride, ammonium niobate oxalate and niobium oxalate; the titanium source is one of titanium sulfate, metatitanic acid, tetrabutyl titanate and isopropyl titanate; the organic solvent is one of ethanol, methanol, cyclohexane, isopropanol, glycerol, tetrahydrofuran, N-methylpyrrolidone and ethylene glycol, or a combination of several of them; the surfactant is one of urotropine, hexadecyltrimethylammonium bromide, ethanolamine and polyvinylpyrrolidone; the alkali source is ammonia water, potassium hydroxide and sodium hydroxide; the alkali source is 1.5-6 times the molar ratio of the niobium source, and the amount of the surfactant is 3-5 times the molar ratio of the niobium source.

4. The preparation method according to claim 1, characterized in that: In step 4, the mass ratio of the titanium niobium oxide composite precursor grown on the carbon tube to the boron powder is 1:0.6-1.

8.

5. The preparation method according to claim 1, characterized in that: In step 4, the boron source is one of sodium borohydride, boron powder and boron dioxide.

6. The preparation method according to claim 1, characterized in that: In step 4, the high temperature calcination temperature in the tubular furnace is 600-900° C., and the calcination time is 3-8 hours.

7. The preparation method according to claim 1, characterized in that: In step 4, the protective atmosphere of the tubular furnace is one of a mixed gas of argon and hydrogen, argon, nitrogen, and a vacuum atmosphere.

8. An application of a boron-doped flaky defect niobium-titanium oxide material grown on a carbon tube prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The boron-doped flaky defect niobium-titanium oxide material grown on the carbon tube and the active material selenium powder are ground and mixed into a uniform powder, and then transferred to a tubular furnace in an argon atmosphere for high-temperature constant-temperature calcination to obtain a selenium- and boron-doped flaky defect niobium-titanium oxide composite material grown on the carbon tube, which is used as the positive electrode active material of the lithium-selenium battery; or used alone as a catalyst for the adsorption of polyselenides.

9. The use according to claim 8, characterized in that: The mass ratio of the boron-doped flaky defect niobium-titanium oxide material grown on the carbon tube to the active material selenium powder is 3-5:2-1.

10. The use according to claim 8, characterized in that: The calcination constant temperature of the tubular furnace is 240-270°C and the calcination time is 10-18h.

Citation Information

Patent Citations

  • Preparation method of titanium-niobium oxide nano rod / carbon nano fiber array electrode

    CN107808956A

  • Lithium-selenium battery

    CN116686130A

  • Interactive artificial intelligence-based sales information generation system

    KR1020240164697A

  • Lithium-selenium battery containing an electrode-protecting layer and method of improving cycle-life

    US20190393510A1